Conceptualising the socio-material context: an ethical enquiry into the contextual materialisation of paradoxes in transport logistics - Mies, Annika (Journal of business ethics, 2026)
We propose a conceptualisation of the socio-material context of paradox theory by empirically investigating multilevel paradoxes arising in the context of professional drivers and advanced driver assistance systems. Truck and bus drivers face complex work environments, external pressures, and fluctuating stress levels, which result in tensions with ethical implications that extend their immediate work and organisational settings. Whilst the quantum approach to paradox theory emphasises the relevance of individuals’ socio-material contexts in shaping their experiences of paradoxes (i.e. salience), its conceptualisation has remained abstract. Based on interviews with truck drivers, bus drivers, and managers of German logistics companies, we identified latent nested paradoxes at individual, organisational, and systemic levels, which become salient depending on variations in socio-material contexts. These socio-material contexts comprise social (e.g. personal values, prior experience), technical (e.g. work routines, technological artefacts), and external environmental factors (e.g. regulatory frameworks, societal perceptions). Synthesising socio-technical systems theory and paradox theory, we conceptualised the socio-material context as a dynamic interplay between social, technical, and environmental elements, offering a nuanced understanding of the conditions under which latent tensions can become salient and persistent. This operationalisation of the socio-material context further provides leverage to the potential mitigation of paradoxical salience. From a multilevel perspective, we shed light on the system-wide complexity of paradoxical tensions in the transport logistics sector. Our research highlights theoretical, ethical, and sustainability implications of understanding and reshaping the features of the socio-material context to address sustainability paradoxes and moral dilemmas and contribute to improved social sustainability in transport logistics.